PERBANDINGAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA Daily ChemQuiz DAN PERMAINAN Ranking One Chemistry Quiz - Tiya Rurin Utari; Amrul Bahar; Dewi Handayani (ALOTROP, 2017)
[COMPARISON OF STUDENTS LEARNING RESULT USING MEDIA Daily Chem Quiz AND GAMES Ranking One Chemistry Quiz]  The aim of this research is to know the difference of students' chemistry learning result using Daily Chem Quiz (DC Quiz) and Ranking One Chemistry Quiz (ROC Quiz) media at class X MIPA in SMA Negeri 1 Bengkulu Tengah 2016 / 2017 academic year. This research is quasi research experiment. The independent variables are DC Quiz and ROC Quiz media, the dependent variable is the students' learning result and the control variable is the Think-Pair-Share (TPS) cooperative learning methods. The population is all students of class X MIPA at 2016/2017 academic year consisting of 4 classes, and to determine the sample is done by homogeneity test then taken by simple random sampling. The selected sample is the class X MIPA 3 as experiment class I using DC Quiz and class X MIPA 1 as experimental class II using RC Quiz . Data analysis used were mean score, normality test, homogeneity test, and t test. Based on posttest value of both class, it is known that the average value of posttest at experiment class I is 78.79 and at  experiment class II is 84,77. The result of data analysis shows that the data is normally distributed and has homogeneous variance and obtained t count> ttabel (2,47> 2,39). The results of this study indicate that H0 rejected and Ha accepted in other words there is a significant difference between student learning outcomes using DC Quiz media and RC Quiz media.